Gastropod Community An Vertical Distribution Pattern Of Littoraria Scabra (Linnaeus, 1758) In Mangrove Ecosystem, Tombariri District, Nort Sulawesi - Bilaleya, Iman; Lalita, Jans; Mantiri, Rose O. S. E.; Kepel, Rene Ch.; Lumingas, Lawrence J.; Lohoo, Anneke V. (Jurnal Ilmiah Platax, 2023)
The Coast water of Tombariri District is an area that has a main ecosystem like mangroves, seagrass, and reef. This research is to aim to know the species various, the structure of the gastropod community, and the vertical distribution pattern of Littoraria scabra in the mangrove ecosystem in Tombariri District, North Sulawesi. Process of gastropod sampling horizontally where transects were put horizontal coastline on every location including Mokupa, Elu, and Tambala. Every transect long has 65 m and also has every transect has 15 quadrats where every quadrat is one-meter square. Therefore, every transect has 15 quadrats, so a total of 45 quadrats. Every quadrant was put systematic method, that is, at terrestrial closing mangrove of 5 quadrats, middle mangrove of 5 quadrats, and coast close mangrove of 5 quadrats. Process of sampling particularly L.scabra where taking vertically, especially on microhabitats that is, roots, stems, branches, and leaves of mangroves. High measuring by meter unit, conducted from the ground where L.scabra found at mangrove until the top vegetation. Based on the result of observation on the identification of gastropod sampling found in the mangrove ecosystem, Tombariri District, North Sulawesi as many 235 of individuals consisting of 5 orders, 23 families, and 32 genera having 78 species. The density of species on every location Mokupa, Elu and Tambala, that is, (D) = 4.60, 5.47, and 5.60 in ind/m2, index of diversity,(H) = 2.54, 3.07, and 3.51 and index of dominance, ID = 0.04, 0.07 and 0.13. Keywords: Microhabitat, density, diversity, and dominance Abstrak Perairan pantai Kecamatan Tombariri merupakan daerah yang memiliki ekosistim utama pesisir seperti mangrove, lamun, dan terumbu karang. Penelitian ini bertujuan untuk mengetahui jenis-jenis, struktur komunitas gastropoda dan pola distribusi vertikal spesies Littoraria scabra di ekosistem mangrove Kecamatan Tombariri, Sulawesi Utara. Proses pengambilan sampel gastropoda secara horizontal, di mana transek ditempatkan sejajar garis pantai pada setiap lokasi yakni di Mokupa, Elu, dan Tambala. Panjang setiap transek 65 m dan setiap transek memiliki 15 kuadrat di mana kuadrat berukuran 1 x 1 m. Setiap transek punya 15 kuadrat sehingga total kuadrat seluruh transek adalah 45 kuadrat. Penempatan kuadrat menggunakan metode sistematik yaitu di bagian darat 5 kuadrat, pertengahan 5 kuadrat dan mangrove pinggir laut 5 kuadrat. Proses pengambilan sampel secara vertikal khusus Littoraria scabra, di mikrohabitat akar, batang, cabang dan daun mangrove,Sementara pengambilan sampel L.scabra diukur ketinggian di mana spesies Littoraria scabra ditemukan ldi pohon mangrove dengan menggunakan meteran, dimulai dari dasar sampai ke ujung pohon mangrove. Berdasarkan hasil pengamatan dan identifikasi sampel gastropoda yang ditemukan di ekosistem mangrove Kecamatan Tombariri, Sulawesi Utara ditemukan sebanyak 235 individu yang terbagi ke dalam 5 ordo, 23 famili dan 32 genera dari 78 spesies. Kepadatan Jenis pada masing-masing lokasi = 4,60, 5,47, dan 5,60 ind/m2. Keanekaragaman H’= 2,54, 3,07, dan 3,51. Dominansi C= 0,04, 0,07, dan 0,13. Kata Kunci : Mikrohabitat, Kepadatan, Keanekaragaman, Dominansi.